Cervical spinal epidural abscess following acupuncture and wet-cupping therapy: A case report. (February 2016) - Yao, Yindan; Hong, Wenke; Chen, Huimin; Guan, Qiongfeng; Yu, Hu; Chang, Xianchao; Yu, Yaoping; Xu, Shanhu; Fan, Weinv
Highlights: We report a case of cervical epidural abscess that developed after acupuncture and wet-cupping therapy in China for the first time. Acupuncture and wet-cupping therapy should be taken into consideration as a cause of spinal epidural abscesses. Acupuncture and wet-cupping practitioners should pay attention to hygienic measures. Abstract: Objective: Report of an uncommon complication of acupuncture and wet cupping. Methods: A 54-year-old man presented with neck pain and fever. Magnetic resonance imaging of the cervical spine revealed an epidural abscess at C4 to T2. Results: The symptoms related to epidural abscess resolved partially after treatment with antibiotics. Conclusion: Acupuncture and wet-cupping therapy should be taken into consideration as a cause of spinal epidural abscesses in patients who present with neck pain and fever. Furthermore, acupuncture and wet-cupping practitioners should pay attention to hygienic measures.